Current Clinical Guidelines for the Management of Patients with Allergic Rhinitis - Natal’ya G. Astaf’eva; Aleksander A. Baranov; Elena A. Vishneva; Nikolay A. Daykhes; Aleksander V. Zhestkov; Natal’ya A. Il’ina; Olga V. Karneeva; Elena P. Karpova; Irina A. Kim; Andrey I. Kryukov; Oksana M. Kurbacheva; Raisa Ya. Meshkova; et al. (Педиатрическая фармакология)
The article presents modern approaches to the diagnosis and therapy of patients with allergic rhinitis. The document was developed by the professional association of pediatric specialists — the Union of Pediatricians of Russia — together with leading specialists of the Russian Association of Allergologists and Clinical Immunologists, the National Medical Association of Otorhinolaryngologists and is regularly updated taking into account the latest data on the effectiveness and safety of various medical interventions. The article provides information about the epidemiology of allergic rhinitis, provides characteristic diagnostic signs of the disease, allowing for establishment as timely as possible of a correct diagnosis and, taking into account a personalized approach, prescribe effective therapy.